2020
DOI: 10.1111/jpi.12669
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin restores the pluripotency of long‐term‐cultured embryonic stem cells through melatonin receptor‐dependent m6A RNA regulation

Abstract: N6‐methyladenosine (m6A) methylation is the most common and abundant modification on mammalian messenger RNA (mRNA) and regulates the pluripotency of embryonic stem cells (ESCs). Research has shown that melatonin plays a fundamental role in DNA and histone modifications. However, the effect of melatonin on RNA modification is unknown. Here, for the first time, we investigated the effect of melatonin on m6A modifications in long‐term‐cultured ESCs. Pluripotency studies indicated that 10 μmol/L melatonin suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…For example, KLF4 negatively regulated cellular antiviral response by inhibiting the activation of NF-κB by TNF-α and IL-1β ( 19 ). In addition, melatonin was found to stabilize KLF4 by preventing its m 6 A-dependent mRNA decay ( 20 ). However, whether and how KLF4 is regulated by the N 6-methyladenosine (m 6 A) modification via virus–host interaction need to be further elucidated.…”
mentioning
confidence: 99%
“…For example, KLF4 negatively regulated cellular antiviral response by inhibiting the activation of NF-κB by TNF-α and IL-1β ( 19 ). In addition, melatonin was found to stabilize KLF4 by preventing its m 6 A-dependent mRNA decay ( 20 ). However, whether and how KLF4 is regulated by the N 6-methyladenosine (m 6 A) modification via virus–host interaction need to be further elucidated.…”
mentioning
confidence: 99%
“…Numerous studies in recent years have shown that N6methyladenosine (m6A) methylation is a commonly seen modification in eukaryotic messenger RNA (mRNA) and strongly affects many basic biological processes, such as cell differentiation, tissue development and tumorigenesis (9)(10)(11)(12). The level of m6A methylation is regulated by methyltransferases, demethylases, and binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 10 μM melatonin maintained the stemness features of ESCs for more than 90 days (45 passages) via the marked suppression of global m 6 A modification and significant reduction in m 6 A “writer” METTL3 [ 1050 ]. Melatonin treatment decreased m 6 A mRNA methylation and altered the subcellular location of METTL3, preventing m 6 A-dependent mRNA decay to stabilize key pluripotency factors Nanog, Sox2, Klf4, and c-Myc [ 1050 ], known to be destabilized by m 6 A methylation [ 1051 ]. It has been proposed that melatonin could decrease METTL3, increasing ESC pluripotency via the MT1-JAK2/STAT3-Zfp217 signal axis.…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…Zinc finger protein 217 (ZFP217) has been reported to activate pluripotency genes and sequester METTL3 [ 1052 ]. Using doxycycline to induce an 85% knockdown of ZFP217 in ESCs treated with melatonin, or the depletion of melatonin receptor 1 (MT1), failed to produce similar effects of m 6 A modification compared to wild-type ESCs treated with melatonin [ 1050 ]. However, if knocking down ZFP217 (reduction in ATP by 25% in prostate cancer cells [ 1053 ]) and/or using doxycycline (~80% reduction in ATP in hypoxic stem-like prostate cancer cells [ 1054 ]) lowered ATP production in ESCs used in the experiment [ 1050 ], then it is possible that even in the presence of melatonin, the lack of ATP led to the failure of DDX3, an ATP-dependent helicase that regulates m 6 A mRNA methylation.…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
See 1 more Smart Citation